Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 780 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Spirodela punctata (G.Mey.) C.H.Thomps.", "HasCoordinate is true", "HasGeospatialIssue is false" ] } The dataset includes 780 records from 52 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0061344-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences